Pengembangan E-Worksheet Berbasis Tri-Ko dan PjBL untuk Penguatan Karakter Global Siswa - Ermiyawati, Riris; Zulfiati, Heri Maria; Barriyah, Insanul Qisti (Media Manajemen Pendidikan, 2025)
The character of global diversity is essential for students, as today's world is interconnected without borders. The aim of this study is to determine the content quality of the e-worksheet, its visual design quality, its practicality, and its effectiveness in enhancing students’ global diversity character. This is an R&D study using the ADDIE model. The expert validation test involved three experts specializing in content, media, and practice. The effectiveness test subjects were 18 fourth-grade students from SD N Banjarharjo and SD N Kalibawang. The expert validation results showed that the content quality scored 97% (very appropriate category), and the visual quality scored 91% (very appropriate category). The practicality test resulted in a score of 92%, indicating it is very practical. Meanwhile, the effectiveness test using a paired sample t-test showed an increase in the average score from 1.84 in the pretest to 2.90 in the posttest, with a significance value of 0.000 (< 0.05), indicating a significant difference. Therefore, the product is effective in improving students’ global diversity character.